Impact of Exogenous Shocks on Consumption Approximated by Retail Trade in Croatia (Vallis Aurea, 2020)
This paper analysis the impact of two different types of exogenous shocks on the consumption, approximated by retail trade in Croatia. The aim of this paper is to show that the crisis caused by financial disturbances and the crisis caused by pandemic have different repercussions on movements of interest rates and further impact on consumption. Banks react differently in a crisis that has no cause in the financial sector compared to the crisis caused by disturbances in the financial and banking market as we had in 2008. Therefore, it will be proven that in crisis of 2020, which is more significant in strength than the crisis in 2009, Croatia has pursued a different economic policy, aimed to retaining jobs and maintaining the level of consumption from pre-recession periods. All mentioned emphasizes two facts: 1. The irrational behavior of the state in a crisis caused by disturbances in the financial and banking sector differs to the state reaction to the crisis caused by a pandemic, that has no financial cause; 2. Fear of negative psychological expectations and falling demand and personal consumption, are the most important components in the GDP structure.